Mental health and human rights: An analysis of rights violations and resistance processes - Silva, Joaquim Luiz; Pires, Rosely Silva; Pereira, Socrates da Silva; Oliveira, Everton Conceição; Acker , Brener Araújo (Seven Editora, 2024)
This proposal raises some questions about human rights violations by state actors. To this end, we seek fragments in the history of institutionalized violence in Brazil, to demonstrate how the state, through the public security apparatus, even after the period of re-democratization of the country, continues in the name of fighting crime by invading homes, using repressive methods that depend on the violation of the most elementary human rights. This under the applause of a middle class that is increasingly thirsty for security. DOI:https://doi.org/10.56238/sevened2024.007-056